Geographic imprint and ecological functions of the abiotic component of periphytic biofilms. Issue 4 (25th October 2022) - Sun, Pengfei; Liu, Yingyao; Sun, Rui; Wu, Yonghong; Dolfing, Jan
Abstract : We revealed abiotic components (extracellular polymeric substances, EPSs) in the periphytic biofilms. Further, the effect of the microbial community on the EPS, and the geodistribution patterns and ecological functions of the EPS were studied.